Espírito Santo da Fortaleza de Porcinos: família, herança e autoconstituição quilombola no interior do estado de São Paulo - Sörensen, Sheiva (Universidade Federal de São Carlos, 2022)
The present thesis occupies a place in the works about the remaining communities, dealing, in particular, with an ethnography about the trajectory of a group of relatives-heirs self-identified as remnants of the quilombo of "Espírito Santo da Fortaleza de Porcinos". The lands traditionally occupied by the Porcinos are located in the city of Agudos, in the interior of the State of São Paulo. However, the members of this large family are currently dispersed in some cities, including Agudos, Bauru and other surrounding municipalities. The group's self-identification process gained strength in 2007 because of the contact of some relatives with land regularization policies and with the rights already recognized by law. At an event about family farming promoted by AGRIFAM, one of the leaders came to know that the historical and current condition of the Porcinos could be defined as quilombo remnants, which provided a new alternative to the territorial demands of the group. From this perspective, the Porcinos are currently reflecting on the trajectories of their ancestors at the same time as they idealize new projects. Kinship, alliance, heritage and agglutination converge in this process with the concept of quilombo and with "becoming" quilombola. From this context, the general objective of this work is to treat ethnographically the self-constitution of the group, seeking to apprehend the multiplicity of issues that are revealed in this process, as well as to map the paths and trajectories of the members of this family, ethnographically following their current developments.
Espírito Santo da Fortaleza de Porcinos: quilombola family, inheritance and self-constitution in the interior of the state of São Paulo
Keywords: Quilombo; Herança; Parentesco; Heritage; Kinship; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA DAS POPULACOES AFRO-BRASILEIRAS